A Compact and Efficient U Slot Excited Substrate Integrated Waveguide Based Antenna for 5G-NR Millimeter Wave Band - Nasir, Nida; Bin Jamaluddin, Mohd Haizal; Shahadan, Nor Hidayu; Shairi, Noor Azwan (International Journal of Integrated Engineering, 2025)
In the article, a cubical dielectric resonator antenna is excited through a U-slot aperture utilizing a Substrate Integrated Waveguide feeding mechanism. This antenna works in three different frequency bands of the millimeter range, 25.8, 27.5, and 30.4 GHz, targeting the 5G-NR bands, N257, and N258. The simulated antenna produces a substantial bandwidth of 6.12 GHz (25-31.12 GHz), a peak elevated gain of 8.9 dBi with 98% efficiency. The radiation patterns indicate the absence of backside radiation, validating the broadside transmission of the proposed antenna. All simulations for antenna design were carried out using Ansys HFSS, confirming the antenna’s suitability for high-performance 5G wireless communication systems, including applications in indoor environments, IoT infrastructure, and smart mobility platforms.